The Influence of Services and Facilities On Student Satisfaction (Case Study: Bandar Lampung University Management Students Class Of 2020 - Gaol, Paulina Rose L; Habiburrahman, Habiburrahman (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
Higher education as an institution must be able to provide brilliant solutions that are in accordance with the interests of students, one of which is in the field of services and facilities available at the College. Has a formulation of the problem of how the description of Services and Facilities on Student Satisfaction which is part of the 2020 batch of Management Study Programs at Bandar Lampung University is related to the Services and Facilities provided. The purpose of this study was to investigate the relationship between the level of service and the quality of facilities with the level of student satisfaction in the university environment. This study uses a quantitative approach and applies a descriptive approach. The focus of the study was on Management students in the Class of 2020. Data was collected through the use of a questionnaire with a Likert scale. The sample was determined using the Slovin formula, while data analysis involved Multiple Linear Regression Test utilizing the support of SPSS for Windows version 23.0, and Hypothesis Tests such as T Test and F Test were also conducted. The findings of this study show that Service contributes positively and significantly to the level of Student Satisfaction. Furthermore, the Facility variable also has an impact on the level of Student Satisfaction, and overall, Services, Facilities as a whole have a positive and significant impact on student satisfaction.